Billi ki gardan main ghanti (Ferozsons (PVT) LTD Lahore)
Billi Ki Gardan Mein Ghanti is a fable that illustrates the consequences of impractical ideas through the humorous tale of a cat's bell, exploring themes of wisdom and action.